Liothyronine Therapy in Hypothyroidism - Dinda Aprilia; Eva Decroli; Alexander Kam; Jonggara Oktaviandra Siahaan (Scientific Journal, 2025)
Hypothyroidism is a clinical condition characterized by reduced production of thyroid hormones and is among the most common endocrine disorders, affecting about 3% of the general population, with a higher prevalence in women (5.1%) than in men (0.9%). In Indonesia, the prevalence of hypothyroidism is estimated at 5-10%. Despite achieving normal thyroid stimulating hormone (TSH) levels with levothyroxine (LT4) therapy, many patients continue to experience symptoms like fatigue, depression, and cognitive impairment, which impact their quality of life. A study of 969 hypothyroid patients found that 77.6% were dissatisfied with their treatment and reported low quality of life scores. Although LT4 has been the standard therapy for nearly 50 years due to its stability and the peripheral conversion of thyroxine (T4) to triiodothyronine (T3), recent recommendations from experts in developed countries suggest using liothyronine (LT3) monotherapy or a combination of LT3 and LT4 in selected cases.